A Prey-Predator Model with Michael Mentence Type of Predator Harvesting and Infectious Disease in Prey - Ibrahim, Hiba Abdullah; Naji, Raid Kamel (Iraqi Journal of Science, 2020)
A prey-predator model with Michael Mentence type of predator harvesting and infectious disease in prey is studied. The existence, uniqueness and boundedness of the solution of the model are investigated. The dynamical behavior of the system is studied locally as well as globally. The persistence conditions of the system are established. Local bifurcation near each of the equilibrium points is investigated. Finally, numerical simulations are given to show our obtained analytical results.